Availability of Hydrogen Shapes the Microbial Abundance in Biofilm Anodes based on Geobacter Enrichment. Issue 18 (25th August 2020) - Korth, Benjamin; Kuchenbuch, Anne; Harnisch, Falk
Abstract: Invited for this month's cover picture is the group of Prof. Dr. Falk Harnisch at the Helmholtz Centre for Environmental Research (Germany). The cover picture displays a biofilm anode obtained by electrochemically driven enrichment in a one‐chamber reactor that is dominated by Geobacter but also colonized by methanogens that cross feed from cathodic hydrogen. Read the full text of the Article at 10.1002/celc.202000731 . Abstract : "Geobacter enrichment biofilm anodes are cultivated in one‐chamber and two‐chamber reactors. By applying molecular and microscopic methods, it is demonstrated that the reactor configuration and thus, the hydrogen availability shape microbial abundance and composition within these biofilms…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.202000731 .